Implementasi Teknologi Load Balancing Dua Jalur Internet Service Provide (ISP) menggunakan Metode Per Connection Classifier (PCC) di Pondok Pesantren Yasin Kudus - Anif, Muhammad; Widodo, Sarono; Hidayat, Sidiq Syamsul; Triyono, Eddy; Wasito, Endro; Wardihani, Eni Dwi; Anggraeni, Sri; Pramono, Subuh; Yulianto, Taufiq; Iswanti, Iswanti; Firmansyah, Ardi (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2018)
Access to the Internet, as well as Information and Communication Technology (ICT) in general, is nowincreasingly needed by the wider community, including by the pesantren community. The community of pesantren needInternet media to expand access to sources of knowledge, publish the activities of pesantren, as well as a medium ofpesantren da?wah in cyberspace. Due to the lack of use of ICT in pesantren, then not all ICT components can be utilized.This community service partner is Pesantren Yasin Kudus, who wants to apply ICT to support learning for students(called santri), by providing smooth and healthy Internet access at affordable cost. The problem faced is Internet accessthat only depends on one Internet Service Provider (ISP), so if the connection on the ISP is failed then Internet accessbecomes disturbed. The solution offered is the use of two ISP connections as an Internet access network, by applying loadbalancing technology using Per Connection Classifier (PCC) method so that loading of traffic on both ISPs can bebalanced. With this program, partners can utilize Internet access from both ISPs optimally